Invariance of sliding motions with respect to control matrix - Kotowski, S. (Archives of Mechanics, 1996)
The object of this paper is the proof of the theorem that the sliding solutions of systems of differential equations with discontinuous functions, with a linear control input, which describe mechanical systems, are independent of parameters of the control input matrix.